INTERDISCIPLINARY COMPETENCE AND INDICATORS OF THE QUALITY OF PROFESSIONAL TRAINING OF STUDENTS IN VOCATIONAL COLLEGES - Боско, Н.М. (SWorldJournal, 2024)
The article examines the essence of the concepts of "interdisciplinary competence" and "quality of professional training" of students in vocational colleges. Using a normative approach, indicators of education quality were identified. By synthesizing rese